(3EQTGO GdYbd GdSdje Edi eRGjG GdcJGH GdcQjes - (3eMeO Hf eMeO Hf eUWai GdYeGOj, Gdehdi CHh GdSYhO,J (B982 (3g` s ((3YHO GdbGOQ Hf CMeO GdEeGe s)
(3ChdgG (B:s
(3SHMGfg ef CQSd QShdg HGdgOi hOjf GdMb hHYO Ef GdZGjI GdbUhi ef JMQjQ fSNI GdYGde djSJ EdG eYQaI GdUGfY GdeLjO hdG SHjd Edi Pdc GdeWdH s
(3BNQgG (B:s
(3BNQg BNQ JaSjQ ShQI GdESQGA s
(3ShQJi GdfMd hGdESQGA de jcJHgeG GdfGSN EfeG cJHgeG ZjQg HNW eMOK hGdBjGJ ajgeG HGdMeQIs
(3hYdi GdfSNI JbjjOGJs
(3hJedc SfI (B1172 (3g` s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs